Effect of phosphorus application and soybean cultivar on grain and dry matter yield of subsequent maize in the tropical savannas of north eastern Nigeria - Kamara, A.Y.; Kwari, J.; Ekeleme, F.; Omoigui, L.O.; Abaidoo, Robert C. (2008)
Soybean can contribute to soil N, which may partly be used to improve maize production in northeast Nigeria. However, the efficiency of soybean to fix N can be limited by soil P deficiency. This study evaluated the effect of P application and soybean cultivars on dry matter and grain yield of subsequent maize for two years (2005 - 2006) at Miringa and Azir. Experimental design was a split-plot with three replications. The main plots contained P levels of 0, 20 and 40 kg P/ha and subplots had four soybean cultivars. Maize was planted in the harvested soybean plots. Application of P to soybean at 20 and 40 kg/ha significantly increased dry matter and grain yield of succeeding maize. Differences in grain yield were significant between all P rates in Miringa (2005) and Azir (2006) but only between 0 and 40 kg P/ha in Azir (2005) and Miringa (2006). The grain yields of maize following late-maturing soybean cultivars were significantly higher than those following the early maturing cultivars in 2005. The maize yield increases could however, not be explained by total soil N, available P, and N and P uptake. Other rotation effects beyond N supply by the preceding soybean may be responsible for the yield increases of maize.